Case report: Dramatic impact of DNA next generation sequencing results using specific targeted therapies—ALK and PIK3CA - Cullum, Stav; Vang, Hlu; Glover, Michael; Alammarah, Howra; Morton, Heather; Pham, Nancy; Rahman, Mobeen; Khan, Saad A. (Frontiers in Oncology, 2024)
In the era of targeted therapies, the clinical importance and utility of next-generation sequencing (NGS) has expanded significantly. Owing to the relative ease and financial feasibility of NGS, the use of personalized treatment strategies has the potential to revolutionize cancer care. In this case report, we explored the use of NGS in salivary gland carcinoma (SGC) and spindle cell neoplasm of the scalp. In our patient with SGC, NGS revealed a GPHN-ALK variant that allowed off-label treatment with alectinib, with a remarkable response in primary and metastatic foci. Similarly, the use of NGS in a cutaneous neoplasm in which no definitive diagnosis could be reached by pathology and which had progressed through standard of care treatment elucidated a PIK3CA mutation in which alpelisib was added and ultimately halted POD. Here, we discuss the use of NGS, future projections, and our recommendations.